Caseload distribution of general surgeons in regional Australia: is there a role for a rural surgery sub‐specialization?. Issue 6 (5th June 2018) - Bappayya, Shaneel; Chen, Fiona; Alderuccio, Megan; Schwalb, Heinrich
Abstract : Background: Rural and regional Australia presents a unique challenge in the delivery of surgical services by virtue of its geographical vastness and low population density. While up to 33% of Australians live in rural or regional areas, only 14.8% of surgeons work in a rural or regional area. Data regarding the caseload distribution of general surgeons working in a regional setting in Australia remain scarce. In order to better examine the training needs of rural general surgeons, this study aims to examine the caseload distribution of general surgeons working in regional Australia. Methods: A retrospective review of surgical procedures carried out by general surgeons at Albury Base Hospital between September 2006 and December 2014 was carried out. Surgical procedures were grouped according to the classifications of the Royal Australasian College of Surgeons Morbidity and Audit Logbook Tool. Results: During the study period, 21 652 procedures were carried out by general surgeons. A total of 58.7% (12711) of these procedures consisted of general surgical procedures and 35.9% (7763) were endoscopic procedures. A total of 5.4% of procedures carried out by general surgeons fell outside the scope of traditional general surgery, including cardiothoracic, orthopaedic, ear, nose and throat, neurosurgical, vascular and urological procedures. All general surgeons performed operations in surgical specialities outside of general surgery. Conclusion: This study adds weight to the value of a broad skill set in provision of surgical services in a rural setting.